FAKTOR KEMENANGAN CALON LEGISLATIF M. NUR HASAN DAN H. M. WARSIT PADA PEMILU TAHUN 2019 - Salsabila Yumna Fadhila; Dewi Erowati (Journal of Politic and Government Studies, 2021)
In the 2019 election, 49 legislative candidates were former corruption convicts and 8 of them won back votes. This political phenomenon contains a question mark on how a former corruptor can be re-elected, this is very important to be examined further because it is related to the problem of corruption eradication in Indonesia. Therefore, this study discusses the winning factors for the legislative candidates M. Nur Hasan and H. M. Warsit as former corruption convicts. The goal is to find out how legislative candidates for former corruption convicts in the 2019 elections can be re-elected. The theories used in this research are political marketing theory, political machines, and social capital. This study used qualitative research methods. The data collection technique was carried out through interviews with M. Nur Hasan, SH, MH and HM Warsit, S.Pd, SH, MM, the commissioners of the Central Java KPU, the Success Team, non-voters, and academic figures. The results of this study found that there were three factors that influenced the victory of M. Nur Hasan and H. M. Warsit, namely targeted political marketing, the power of the political machine, and strong social capital ownership. These three factors are important factors in the election of candidates for legislative members with the status of former corruption convicts in Central Java, although in the end these factors still have their own share in influencing the election of the candidate. The social capital factor is the most dominant factor that each candidate has. This is because M. Nur Hasan is a political figure and businessman who has long been a member of the Rembang Regency DPRD in the previous period. Likewise with H. M. Warsit, who in fact is a political figure who was the chairman of the DPRD Blora Regency for two periods